Smart Water Dispenser Monitoring System - Syed Haidzir, Syed Hazwan Hafiz; Hisham, ohamad Aziq Haiqal; Omar, Mastura (2020)
People become dehydrated if they do not drink enough water. To solve this problem, it is essential to monitor how much water that consumed every day. So, objective of this product is to develop smart monitoring water dispenser using Arduino Mega 2560 as microcontroller that controlled the amount of water dispensed by this water dispenser. For this product, button system is used to determine the volume of water to drink. Every button has their own amount of water that they will dispense. The amount of water will then be being recorded and display to LCD and app Blynk in your smartphone.